Epalrestat pharmaceutical composition and preparation method thereof
The granules of epalstat pharmaceutical composition prepared by extrusion rounding process solve the problems of low dissolution and large differences between tablets in existing epalstat tablets, and achieve the effect of high bioavailability and differences between small tablets.
Patent Information
- Application Number
- CN202411888614.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The average dissolution of existing epalstat tablets is low, and the dissolution varies greatly between tablets, resulting in low drug bioavailability and affecting clinical effect.
Epastat pharmaceutical composition granules are prepared by extrusion rounding process, and the composition contains epastat, filler, disintegrant, surfactant and binder. By optimizing the ratio and process parameters, the fluidity and dissolution performance of the granules are improved.
The high average dissolution (greater than 95%) and small differences in dissolution between tablets (RSD less than 3%) were achieved, which improved the bioavailability and clinical value of the drug.
Smart Images

Figure BDA0005200008640000061 
Figure BDA0005200008640000062 
Figure BDA0005200008640000063
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and relates to an epalrestat pharmaceutical composition and a preparation method thereof. Background Art
[0002] Diabetes is a common chronic disease. According to statistics, the number of diabetes patients in China in 2021 is about 140 million, and the prevalence rate is as high as 10.6%. Diabetic peripheral neuropathy is one of the most common chronic complications of diabetes. It is characterized by high prevalence, early onset, complex symptoms, and difficulty in cure, and it is more likely to cause serious disability. The occurrence of diabetic peripheral neuropathy is related to the hyperactivity of the polyol pathway, and its pathogenic mechanism is: the osmotic pressure gradient formed by the accumulation of sorbitol in cells and the competitive binding of high levels of glucose with inositol carriers reduce the level of intracellular inositol. Inositol esters are extremely important for maintaining the normal function of cells (especially nerve cells). The depletion of intracellular inositol can seriously affect cell function (such as causing cell membrane Na + -K + -ATPase activity is reduced), which plays an important role in the occurrence and development of certain chronic complications of diabetes (especially neuropathy and nephropathy).
[0003] Epalrestat is the only aldose reductase specific inhibitor currently on the market in China. It can effectively prevent, improve and treat diabetic peripheral neuropathy. It also has a certain therapeutic effect on diabetic macroangiopathy, diabetic nephropathy, etc. It can also increase the generation of oxygen free radicals in neutrophils of diabetic patients and improve the patient's resistance. At the same time, compared with other drugs, epalrestat has a low incidence of adverse reactions and is an effective and safe drug for chronic complications of diabetes, especially diabetic neuropathy. At present, the treatment of mild and severe diabetic neuropathy is mainly aimed at its pathogenesis and improvement of microcirculation, and symptomatic treatment is used when necessary. The most commonly used drugs targeting its pathogenesis are methylcobalamin, lipoic acid, and epalrestat. All three drugs can improve diabetic neuropathy from the root cause of the disease. It can be used alone or in combination with each other, and multiple targets work together.
[0004] Extrusion-spheronization technology is currently the most common and widely used micro-pellet preparation technology. First, the drug and excipients need to be evenly mixed to form wet granules; then they are placed in an extruder and the wet granules are extruded into cylindrical strips by extrusion methods such as spiral propulsion or rolling; then the strips are stacked on the self-rotating friction plate of the spheronizer to disperse them into cylinders with smaller diameters, and rolled into spheres through natural grinding; finally, the formed micro-pellet preparations can be obtained by room temperature drying, oven drying, freeze drying or other drying methods. Wet granulation is a method of adding a binder to the drug powder and preparing granules by agglomerating the powder together through the bridging or bonding effect of the binder.
[0005] At present, the most common process for the production of epalrestat tablets is the wet granulation process. As the most popular production process for industrial production, it is undoubtedly an ideal choice for drugs with good wet and thermal stability. Although epalrestat is relatively stable under wet and hot conditions, the release behavior of its tablets is closely related to the hardness of the preparation, and the particle size distribution of the particles determines its powder properties and directly determines the size of the preparation hardness. The current wet granulation process is difficult to control the particle size distribution well, which also leads to a wide range of particle size distribution, resulting in large intra-batch and inter-batch differences. In addition, as a poorly soluble drug, epalrestat, if the raw material particle size is not well controlled, the dissolution behavior of the preparation is difficult to reach an ideal state. Through research, it was found that the epalrestat tablets currently on the market generally have a low average dissolution rate and a large difference in dissolution between tablets. Summary of the invention
[0006] In order to overcome the defects of the prior art, the present invention provides an epalrestat pharmaceutical composition with a simple preparation process, small intra-batch differences between tablets, good dissolution in a medium simulating the human body environment, good bioavailability of the drug, and improved clinical value of the drug.
[0007] To achieve the above object, the technical solution adopted by the present invention is to use an extrusion spheronization process to prepare epalrestat pharmaceutical composition particles with good fluidity, and the composition particles can be further prepared into clinically acceptable tablets, capsules, etc.
[0008] The present invention is achieved through the following technical solutions:
[0009] An epalrestat pharmaceutical composition comprises the following components: epalrestat, a filler, a disintegrant, a surfactant and a binder, wherein the weight percentage of each component is: epalrestat 25-65%, filler 25-70%, binder 2-8%, disintegrant 2-8%, and surfactant 1-3%.
[0010] In the above-mentioned epalrestat pharmaceutical composition of the present invention, the surfactant is selected from one or more of fatty acid glycerides, sucrose fatty acid esters, sorbitan fatty acids, polysorbate, poloxamer, and sodium dodecyl sulfate.
[0011] Preferably, the surfactant is poloxamer or a combination of poloxamer and other surfactants.
[0012] More preferably, the surfactant is poloxamer 188, a combination of poloxamer 188 and one of fatty acid glycerides, sucrose fatty acid esters, sorbitan fatty acids, polysorbate, and sodium lauryl sulfate; preferably poloxamer 188, a combination of poloxamer 188 and polysorbate, and a combination of poloxamer 188 and sodium lauryl sulfate.
[0013] When the surfactant is a combination of poloxamer 188 and polysorbate, the mass ratio of poloxamer 188 to polysorbate is 2:3-3:1, more preferably 1:1-3:1.
[0014] When the surfactant is a combination of poloxamer 188 and sodium lauryl sulfate, the mass ratio of poloxamer 188 to sodium lauryl sulfate is 1:1-3:2.
[0015] In the above-mentioned epalrestat pharmaceutical composition of the present invention, the filler is selected from at least one of silicified microcrystalline cellulose, cellulose lactose and starch.
[0016] The disintegrant is selected from one or more of carboxymethylcellulose calcium, carboxymethylcellulose, low-substituted hydroxypropyl cellulose, cross-linked polyvinyl pyrrolidone, and cross-linked carboxymethylcellulose sodium;
[0017] Preferably, the disintegrant is carboxymethylcellulose calcium, cross-linked carboxymethylcellulose sodium, or a combination thereof, or a combination thereof with other disintegrants;
[0018] More preferably, the disintegrant is calcium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked sodium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked polyvinyl pyrrolidone, a combination of calcium carboxymethylcellulose and low-substituted hydroxypropyl cellulose, cross-linked sodium carboxymethyl cellulose, a combination of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, or a combination of cross-linked sodium carboxymethyl cellulose and sodium starch glycolate.
[0019] When the disintegrant is a combination of calcium carboxymethylcellulose and croscarmellose sodium, the mass ratio of calcium carboxymethylcellulose to croscarmellose sodium is 1:3 to 3:1, preferably 2:3 to 3:2.
[0020] When the disintegrant is a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone, the mass ratio of carboxymethylcellulose calcium to cross-linked polyvinyl pyrrolidone is 2:3 to 3:2.
[0021] When the disintegrant is a combination of carboxymethylcellulose calcium and low-substituted hydroxypropyl cellulose, the mass ratio of carboxymethylcellulose calcium to low-substituted hydroxypropyl cellulose is 1:3 to 2:3.
[0022] When the disintegrant is a combination of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, the mass ratio of cross-linked sodium carboxymethyl cellulose to low-substituted hydroxypropyl cellulose is 1:3 to 3:2.
[0023] When the disintegrant is a combination of cross-linked sodium carboxymethyl cellulose and sodium starch glycolate, the ratio of cross-linked sodium carboxymethyl cellulose to sodium starch glycolate is 1:1 to 3:2.
[0024] The binder is selected from at least one of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose and cellulose acetate;
[0025] The present invention preferably comprises the following epalrestat pharmaceutical composition, wherein:
[0026] The filler is silicified microcrystalline cellulose, the binder is hydroxypropyl cellulose, the disintegrant is calcium carboxymethyl cellulose, a combination of calcium carboxymethyl cellulose and cross-linked sodium carboxymethyl cellulose, and a combination of calcium carboxymethyl cellulose and cross-linked polyvinyl pyrrolidone, and the surfactant is poloxamer 188, a combination of poloxamer 188 and polysorbate, and a combination of poloxamer 188 and sodium lauryl sulfate.
[0027] Preferably, in the above-mentioned epalrestat pharmaceutical composition of the present invention, the weight percentages of various raw materials and auxiliary materials are as follows: epalrestat 30-55%, silicified microcrystalline cellulose 35-60%, carboxymethylcellulose calcium, a combination of carboxymethylcellulose calcium and cross-linked sodium carboxymethyl cellulose, a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone 3-7%, poloxamer 188, a combination of poloxamer 188 and polysorbate, a combination of poloxamer 188 and sodium lauryl sulfate 1.5-2.5%, and hydroxypropyl cellulose 3.5-6.5%.
[0028] Preferably, the weight percentage of each raw material and auxiliary material in the above-mentioned epalrestat pharmaceutical composition of the present invention is as follows: epalrestat 40-50%, silicified microcrystalline cellulose 38-48%, a combination of carboxymethylcellulose calcium and cross-linked carboxymethylcellulose sodium, or a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone 4-5%, a combination of poloxamer 188 and polysorbate 1.8-2.2%, and hydroxypropyl cellulose 4-6%.
[0029] In the combination of calcium carboxymethyl cellulose and cross-linked sodium carboxymethyl cellulose, the mass ratio of calcium carboxymethyl cellulose to cross-linked sodium carboxymethyl cellulose is 2:3 to 3:2, more preferably 1:1.
[0030] In the combination of calcium carboxymethyl cellulose and cross-linked polyvinyl pyrrolidone, the mass ratio of calcium carboxymethyl cellulose to cross-linked polyvinyl pyrrolidone is 2:3 to 3:2.
[0031] In the combination of poloxamer 188 and polysorbate, the mass ratio of poloxamer 188 to polysorbate is 1:1-3:2, preferably 3:2.
[0032] The present invention also provides a method for preparing the above-mentioned epalrestat pharmaceutical composition, comprising the following steps:
[0033] (1) sieving epalrestat, filler, disintegrant, surfactant and binder respectively;
[0034] (2) According to the prescribed amount, the sieved epalrestat, filler, disintegrant, surfactant and binder are mixed with a wetting agent to make a soft material, and then spheronized by extrusion to obtain micropellets, which are then dried and granulated to obtain epalrestat pharmaceutical composition granules.
[0035] The wetting agent in step (2) is selected from at least one of ethanol and water, preferably a 30% to 70% ethanol aqueous solution or water.
[0036] The advantage of the extrusion spheronization process compared to other processes is that it can better ensure the fluidity of the particles to meet production needs.
[0037] The epalrestat pharmaceutical composition particles are added with a prescribed amount of lubricant, mixed evenly, tableted, and a proper amount of coating material is added as required, and after coating, tablets of the epalrestat pharmaceutical composition are obtained.
[0038] The lubricant is selected from at least one of magnesium stearate, sodium stearyl fumarate, talc and silicon dioxide; preferably sodium stearyl fumarate.
[0039] The amount of lubricant is 0.3-1.5%, preferably 0.5-0.9%.
[0040] In the preparation method of the epalrestat pharmaceutical composition of the present invention, after the raw materials are crushed and sieved, the particle size (D90) of epalrestat is less than 60 μm.
[0041] Preferably, after the raw material is crushed and sieved, the particle size (D90) of epalrestat is less than 35 μm.
[0042] In order to prevent the material from agglomerating, the auxiliary materials should be sieved through an 80-mesh sieve before use.
[0043] The present invention also provides tablets of the epalrestat pharmaceutical composition prepared by the above preparation method.
[0044] The present invention finds through research that when epalrestat is crushed to a particle size (D90) of 60 μm, the particle size (D90) of epalrestat is small, the electrostatic effect is strong, and the particle fluidity is poor during tableting. A prescribed amount of epalrestat and a prescribed amount of auxiliary materials are made into a soft material by extrusion and spheronization to prepare micropills, which significantly improves fluidity, significantly improves the average dissolution rate of the prepared epalrestat tablets, reduces the dissolution rate difference between tablets, and improves the quality of the epalrestat tablets.
[0045] The present invention also provides use of the epalrestat pharmaceutical composition or the epalrestat pharmaceutical composition tablet in preparing an aldose reductase inhibitor or a drug for treating diabetic neuropathy.
[0046] The technical solution of the present invention has the following advantages:
[0047] (1) The selected extrusion spheronization process effectively improved the problem of poor particle flowability and large intra-batch variation of this product;
[0048] (2) The epalrestat pharmaceutical composition of the present invention fully considers the composition and ratio of each raw material and auxiliary material. Each raw material and auxiliary material interact with each other at their specific ratio, so that the prepared epalrestat tablets not only have a high average solubility (greater than 95%), but also have a small difference in solubility between tablets (RSD less than 3%), and the quality is significantly improved;
[0049] (3) The preparation method of the epalrestat composition tablet of the present invention comprises crushing epalrestat to a particle size (D90) of ≤60 μm, and simultaneously using a prescribed amount of epalrestat and a prescribed amount of auxiliary material wetting agent to make a soft material to prepare micropellets by extrusion and spheronization, which not only significantly improves the particle fluidity, but also improves the average dissolution rate of the prepared epalrestat composition tablet, and reduces the inter-tablet difference in dissolution rate. The epalrestat composition tablet prepared by the present invention has a simple preparation process, low cost, and considerable economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The dissolution curves of the epalrestat composition tablets of Examples 6 to 10 are shown. DETAILED DESCRIPTION
[0051] Dissolution test method:
[0052] The determination was carried out according to the paddle method, with 900 ml of pH 7.5 phosphate buffer as the dissolution medium, the medium temperature being 37°C, the rotation speed being 100 rpm, and the operation being in accordance with the law. Samples were taken after 5, 10, 15, 30, 45 and 60 min, respectively, the dissolution was filtered, 4 ml of the initial filtrate was discarded, 2 ml of the subsequent filtrate was accurately measured, placed in a 10 ml volumetric flask, and diluted to the scale with the dissolution medium as the test solution, and the sample absorbance was determined.
[0053] Example 1 Screening of preparation process
[0054] prescription:
[0055]
[0056] The particle size D90 of epalrestat was 30 μm.
[0057] Wet granulation, dry granulation, top spray granulation, centrifugal granulation and extrusion spheronization were selected to prepare drug-containing granules, wherein the solvent selected for wet granulation, top spray granulation, centrifugal granulation and extrusion spheronization was purified water.
[0058] Table 1 Comparison of key indicators of drug-containing granules prepared by different processes
[0059]
[0060] The main methods for characterizing powder fluidity are: angle of repose method and Hausner ratio (HR) method. Ipalrestat itself has poor powder properties. Its fluidity must be improved through a granulation process. The closer the HR value is to 1.0, the better its fluidity. When HR>1.25, its fluidity is poor. Generally speaking, the smaller the angle of repose, the smaller the friction, and the better the fluidity. If the angle of repose of the material is ≤30°, it proves that it has good fluidity. Angle of repose ≤40° can meet the fluidity requirements of the production process. On the whole, the extrusion spheronization method is the best process for improving the fluidity of raw materials.
[0061] After the above granules were prepared, sodium stearyl fumarate was added at 0.8% of the prescription amount, and tablets were pressed to examine the weight difference and disintegration time difference.
[0062] Table 2 Comparison of key indicators of drug-containing granules prepared by different processes after tableting
[0063]
[0064] The results showed that the weight difference of the drug-containing granules prepared by the extrusion spheronization method after tableting was the smallest, and the disintegration time measured after taking 6 tablets of each method also had the smallest difference in the extrusion spheronization process. It was preliminarily determined that the extrusion spheronization process could improve the problem of large intra-batch differences in epalrestat tablets.
[0065] The effects of changing factors such as surfactant, disintegrant, filler, particle size, etc. on the dissolution of tablets of the epalrestat composition and the difference between tablets were investigated below.
[0066] Example 2 Screening prescription of surfactant:
[0067]
[0068] The particle size D90 of epalrestat was 28 μm.
[0069] The preparation method is as follows:
[0070] (1) Mix the weighed raw and auxiliary materials thoroughly to ensure that the materials are mixed evenly;
[0071] (2) adding purified water to the solid mixture obtained in step (1), and stirring thoroughly to prepare a soft material;
[0072] (3) The soft material obtained in step (2) is passed through an extrusion device, wherein the mesh size of the extrusion device is 1.0 mm.
[0073] (4) The extruded soft material obtained in step (3) is placed in a spheronization device, subjected to shear spheronization at a rotation speed of 60 Hz, and dried at 60° C. to obtain drug-loaded particles.
[0074] (5) Add magnesium stearate to the drug-containing granules obtained in step (4), mix well and then compress into tablets.
[0075] The effects of different surfactants on the dissolution and inter-tablet variation of tablets of the epalrestat composition are shown in Table 3.
[0076] Table 3 Screening of different surfactants
[0077]
[0078] When different surfactants were used alone, epalrestat reached more than 90% dissolution at 60 minutes, but the intra-batch differences of tablets prepared with different surfactants were very different. Among them, the dissolution rate of the formulation with poloxamer 188 as the surfactant was higher than that of the formulation with other surfactants at each time point, and the dissolution trend of the formulation with polysorbate as the surfactant was close to that of poloxamer 188. The intra-batch differences of the formulations with polysorbate or poloxamer 188 alone were smaller than those of other surfactants.
[0079] Based on the above results, we used a mixture of poloxamer 188 and polysorbate as a surfactant to investigate the effects of different proportions of the mixture of poloxamer 188 and polysorbate on the dissolution of tablets and intra-batch differences. The results are shown in Table 4. The particle size D90 of epalrestat was 33 μm.
[0080] Table 4 Screening of the ratio of poloxamer 188 to polysorbate
[0081]
[0082] As can be seen from Table 4, when poloxamer 188 and polysorbate are used in combination, when the ratio of the two is 1:6-6:1, the dissolution in 60 minutes is greater than 90%, and the intra-batch differences are less than 4%. When the ratio of the two is 2:3-3:1, the dissolution in 60 minutes is more than 98%, and the dissolution in 45 minutes is more than 95%, and the intra-batch differences are less than or equal to 3%. When the ratio of the two is 1:1-3:1, the dissolution in 45 minutes is more than 98%, and the intra-batch differences are less than 3%. It can be seen that when poloxamer and polysorbate are used together as surfactants, the best dissolution and relatively smaller intra-batch differences can be achieved under specific ratio conditions.
[0083] The effects of poloxamer 188 combined with other surfactants on the dissolution and inter-tablet variation of tablets of the epalrestat composition were further investigated. The particle size D90 of the raw material was 27 μm.
[0084] Using a mixture of poloxamer 188 and other surfactants as a surfactant, the effects of different mixtures under different proportions as surfactants on the dissolution of tablets and the intra-batch differences between tablets were investigated. The results are shown in Tables 5-8.
[0085] Table 5 Screening of the ratio of poloxamer 188 to fatty acid glycerides
[0086]
[0087] As can be seen from Table 5, when poloxamer 188 is mixed with fatty acid glycerides, when the mass ratio is 1:6-6:1, the dissolution trend in the pH 7.5 medium is relatively fast, and the dissolution reaches more than 90% in 60 minutes, and the intra-batch difference is less than 4%; when the ratio is 1:3-3:1, the dissolution in the pH 7.5 medium is faster, and the dissolution can reach more than 98% in 60 minutes, but the intra-batch dissolution RSD at 60 minutes does not improve significantly, and its RSD is greater than 3%.
[0088] Table 6 Screening of the ratio of polysorbate to fatty acid glyceride
[0089]
[0090] As can be seen from Table 6, when polysorbate and fatty acid glyceride are mixed, when the mass ratio is 2:3-6:1, the dissolution trend in the pH 7.5 medium is relatively fast, the solubility is greater than 95% at 60 min, and the RSD is less than or equal to 4%; when the ratio is 1:1-3:1, the dissolution in the pH 7.5 medium is faster, the solubility is greater than 98% at 60 min, but the improvement of the RSD of the intra-batch dissolution at 60 min is not obvious, and the RSD is greater than 3%.
[0091] Table 7 Screening of the ratio of poloxamer 188 to sodium lauryl sulfate
[0092]
[0093] As can be seen from Table 7, when Poloxamer 188 and sodium dodecyl sulfate are mixed, when the mass ratio is 1:1 to 3:2, the dissolution trend in the pH 7.5 medium is relatively fast, the solubility is greater than 98% at 60 min, and the RSD is less than 3%; when the ratio is 3:2, the dissolution in the pH 7.5 medium is faster, and the intra-batch difference is minimal.
[0094] Table 8 Screening of the ratio of polysorbate to sodium lauryl sulfate
[0095]
[0096] As can be seen from Table 8, when polysorbate and sodium dodecyl sulfate are mixed and used in different proportions, although the dissolution rate can reach more than 95% in 60 minutes, the RSD improvement is not obvious and is greater than 3%.
[0097] A comprehensive comparison of various surfactants and their combinations shows that when the surfactant is poloxamer 188, a combination of poloxamer 188 and polysorbate, and a combination of poloxamer 188 and sodium dodecyl sulfate, under specific ratio conditions, not only can the dissolution rate reach more than 95% in 60 minutes, but the RSD is less than 3%.
[0098] Example 3: Effect of Poloxamer 188 and Sodium Lauryl Sulfate in a Ratio of 3:2 as Surfactants on the Dissolution and Intra-batch Variation of Epalrestat
[0099] prescription:
[0100]
[0101] The preparation method is as follows:
[0102] (1) Mix the weighed raw and auxiliary materials thoroughly to ensure that the materials are mixed evenly;
[0103] (2) adding purified water to the solid mixture obtained in step (1), and stirring thoroughly to prepare a soft material;
[0104] (3) The soft material obtained in step (2) is passed through an extrusion device, wherein the mesh size of the extrusion device is 1.0 mm.
[0105] (4) The extruded soft material obtained in step (3) is placed in a spheronization device, subjected to shear spheronization at a rotation speed of 60 Hz, and dried at 60° C. to obtain drug-loaded particles.
[0106] (5) Add magnesium stearate to the drug-containing granules obtained in step (4), mix well and then compress into tablets.
[0107] Table 9 Screening of different particle sizes
[0108]
[0109] The dissolution rate of the formulation with raw materials of D90<60μm at each time point is higher than that of the formulation with other raw material particle sizes. The results show that the formulation with raw materials of D90<60μm can obtain a preparation with faster dissolution. When D90<60μm, the RSD value of 60min is less than 3.0%, indicating that the increase of particle size will increase the intra-batch difference. When the raw material D90<35μm, the dissolution rate and RSD of 60min reach the most ideal state.
[0110] Example 4: Effect of Poloxamer 188 and Polysorbate 3:2 as Surfactants on the Dissolution and Batch Difference of Epalrestat
[0111] prescription:
[0112]
[0113] The preparation method is as follows:
[0114] (1) Mix the weighed raw and auxiliary materials thoroughly to ensure that the materials are mixed evenly;
[0115] (2) adding purified water to the solid mixture obtained in step (1), and stirring thoroughly to prepare a soft material;
[0116] (3) The soft material obtained in step (2) is passed through an extrusion device, wherein the mesh size of the extrusion device is 1.0 mm.
[0117] (4) The extruded soft material obtained in step (3) is placed in a spheronization device, subjected to shear spheronization at a rotation speed of 60 Hz, and dried at 60° C. to obtain drug-loaded particles.
[0118] (5) Add magnesium stearate to the drug-containing granules obtained in step (4), mix well and then compress into tablets.
[0119] Table 10 Screening of different particle sizes
[0120]
[0121] Conclusion: When poloxamer 188: polysorbate = 3:2, the dissolution rate of the formulation with raw material D90 < 60 μm at each time point is higher than that of the formulation with other raw material particle sizes. The results show that the formulation with raw material D90 < 60 μm can obtain a preparation with faster dissolution. When D90 < 60 μm, the RSD value of 60 min is less than 3%, indicating that the increase in particle size will increase the intra-batch difference. When the raw material D90 < 35 μm, the 60 min dissolution rate and RSD are both ideal.
[0122] Example 5 Screening of disintegrants
[0123] A mixture of poloxamer 188 and polysorbate 3:2 was used as a surfactant to investigate the effects of different disintegrants on the dissolution and batch-to-batch variation of tablets.
[0124] prescription:
[0125]
[0126] The raw material particle size D90 is 30 μm.
[0127] The preparation method is as follows:
[0128] (1) Mix the weighed raw and auxiliary materials thoroughly to ensure that the materials are mixed evenly;
[0129] (2) adding purified water to the solid mixture obtained in step (1), and stirring thoroughly to prepare a soft material;
[0130] (3) The soft material obtained in step (2) is passed through an extrusion device, wherein the mesh size of the extrusion device is 1.0 mm.
[0131] (4) The extruded soft material obtained in step (3) is placed in a spheronization device, subjected to shear spheronization at a rotation speed of 60 Hz, and dried at 60° C. to obtain drug-loaded particles.
[0132] (5) Add magnesium stearate to the drug-containing granules obtained in step (4), mix well and then compress into tablets.
[0133] Table 11 Screening of different disintegrants
[0134]
[0135] When disintegrants were used alone, the dissolution rates of formulations with carboxymethylcellulose calcium or cross-linked carboxymethylcellulose sodium as disintegrants were higher than those of formulations with other disintegrants at all time points, reaching 100% at 60 min, and the intra-batch RSDs were all less than 3%.
[0136] Based on the above results, we expect to obtain a formulation that can achieve complete release and has smaller intra-batch differences by adjusting the combination ratio, in order to obtain a better disintegrant combination than a single disintegrant formulation. The ratio between carboxymethylcellulose calcium and cross-linked carboxymethylcellulose sodium was changed, and the results are shown in Table 12.
[0137] Table 12 Screening of the ratio of calcium carboxymethylcellulose to cross-linked sodium carboxymethylcellulose
[0138]
[0139] It can be seen from Table 12 that when carboxymethyl cellulose calcium and cross-linked sodium carboxymethyl cellulose are mixed, when the ratio of the two is 1:3-3:1, the solubility in 60 minutes is more than 95%, and the RSD is less than 3%; when the mass ratio of the two is 2:3-3:2, the solubility in 60 minutes is more than 98%, and the RSD is less than or equal to 2%; when the mass ratio of the two is 2:3-1:1, the solubility in 60 minutes is more than 98%, and the RSD is less than 2%.
[0140] The effects of the combination of carboxymethylcellulose calcium and other disintegrants on dissolution and RSD were further investigated.
[0141] Table 13 Screening of the ratio of calcium carboxymethylcellulose to cross-linked polyvinyl pyrrolidone
[0142]
[0143] It can be seen from Table 13 that when carboxymethyl cellulose calcium and cross-linked polyvinyl pyrrolidone are mixed and used in a mass ratio of 2:3 to 3:2, the dissolution in the pH 7.5 medium is faster and the intra-batch difference is minimal. The solubility reaches more than 98% at 60 minutes, and the RSD is less than 3%.
[0144] Table 14 Screening of the ratio of calcium carboxymethyl cellulose to low-substituted hydroxypropyl cellulose
[0145]
[0146] As can be seen from Table 14, when carboxymethyl cellulose calcium is mixed with low-substituted hydroxypropyl cellulose at a mass ratio of 1:3 to 2:3, the dissolution in the pH 7.5 medium is faster and the intra-batch difference is minimal. The dissolution rate is more than 98% in 60 minutes, and the intra-batch RSD is less than 3%.
[0147] Table 15 Screening of the ratio of cross-linked sodium carboxymethyl cellulose to low-substituted hydroxypropyl cellulose
[0148]
[0149] It can be seen from Table 15 that when cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose are mixed and used in a mass ratio of 1:3 to 3:2, the dissolution in a pH 7.5 medium is faster and the intra-batch difference is minimal. The dissolution rate reaches more than 95% in 60 minutes, and the intra-batch RSD is less than 3%.
[0150] Table 16 Screening of the ratio of cross-linked sodium carboxymethyl cellulose to sodium carboxymethyl starch
[0151]
[0152] It can be seen from Table 16 that when cross-linked sodium carboxymethyl cellulose and sodium carboxymethyl starch are mixed and used in a mass ratio of 1:1 to 3:2, the dissolution in the pH 7.5 medium is faster and the intra-batch difference is minimal. The solubility reaches more than 98% at 60 minutes, and the intra-batch RSD is less than 3%.
[0153] Example 6 Preparation of Epalrestat Composition Tablets
[0154] prescription:
[0155]
[0156] The preparation method is the same as Example 4.
[0157] The raw material particle size D90 is 28 μm.
[0158] Example 7 Preparation of Epalrestat Composition Tablets
[0159] prescription:
[0160]
[0161] The preparation method is the same as Example 4.
[0162] The raw material particle size D90 is 25 μm.
[0163] Example 8 Preparation of Epalrestat Composition Tablets
[0164] prescription:
[0165]
[0166]
[0167] The preparation method is the same as Example 4.
[0168] The raw material particle size D90 is 21 μm.
[0169] Example 9 Preparation formula of epalrestat composition tablets:
[0170]
[0171] The preparation method is the same as Example 4.
[0172] The raw material particle size D90 is 30 μm.
[0173] Example 10 Preparation formula of epalrestat composition tablets:
[0174]
[0175] The preparation method is the same as Example 4.
[0176] The raw material particle size D90 is 28 μm.
[0177] Example 11 Properties of the epalrestat composition tablets of Examples 6 to 10:
[0178] The dissolution curves of Examples 6 to 10 show that the dissolution rates of the formulations of Examples 6 to 10 are all above 95% at 60 min, while the dissolution rate of the reference preparation: epalrestat tablets developed by Japan Alfracta Pharmaceutical Co., Ltd. (Ono Pharmaceutical) is lower than 95% at 60 min.
[0179] In addition, the intra-batch RSD of Examples 6 to 10 and the reference preparation at 60 min is shown in Table 17.
[0180] Table 17 Dissolution of the formulations of Examples 6 to 10 and intra-batch RSD at 60 min
[0181] Example 6 Example 7 Example 8 Example 9 Example 10 Reference preparation 45min 98 98 97 90 96 88 60min 99 100 99 97 100 94 60minRSD% 2.2 2.5 2.6 2.7 1.4 3.9
[0182] The results show that:
[0183] As shown in Table 17, when the surfactants and disintegrants are different, the RSD of the dissolution rate of the epalrestat tablets prepared in Examples 6 to 10 can be controlled within 3% at 60 minutes, which is better than the reference preparation. It can be seen that when the surfactant is a combination of poloxamer 188 and polysorbate, a combination of polysorbate and fatty acid glyceride, and the disintegrant is a combination of carboxymethylcellulose calcium and cross-linked sodium carboxymethylcellulose, a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone, and a combination of cross-linked sodium carboxymethylcellulose and low-substituted hydroxypropyl cellulose, the RSD value of the dissolution rate at 60 minutes is more significantly improved compared with the reference preparation.
[0184] Example 12 Pharmacokinetics of Epalrestat Tablets of Examples 6 to 10
[0185] A six-cycle six-crossover trial was conducted on 12 subjects. Blood was collected and blood drug concentration was determined at 0h (within 1h before administration) and 0.25h (15min), 0.50h, 0.75h, 1.00h, 1.25h, 1.50h, 1.75h, 2.00h, 2.50h, 3.00h, 3.50h, 4.00h, 5.00h, 6.00h, 8.00h, 10.00h, and 12.00h after administration in each cycle. The concentration of epalrestat in human plasma was determined by liquid chromatography-mass spectrometry (HPLC-MS / MS). Liquid phase conditions were as follows: chromatographic column: AQUASIL C18, 2.1×50.0 mm, 5.0 μm, Thermo; mobile phase A: aqueous solution containing 5 mM ammonium acetate; mobile phase B: acetonitrile; flow rate: 0.700 mL / min; initial organic phase ratio: 15.0%; injection volume: 2.00 μL; autosampler cleaning solution: methanol; autosampler needle washing volume: 500 μL; autosampler needle cleaning immersion time: 2 s; autosampler cleaning mode: Before and after aspiration
[0186] Autosampler cleaning settings: Rinse Pump Then Port; Autosampler cleaning time: 2s; Autosampler temperature: 4°C; Column oven temperature: 40°C. Mass spectrometry conditions: Ion source: Electrospray y Ionization (ESI); ionization mode: negative ion mode; detection mode: multiple reaction monitoring; electrospray voltage: -4500.00 V; vortex ion spray temperature: 550.00 ° C; curtain gas: 35.00 psi; collision cell gas type: 9.00; nebulizer gas: 55.00 psi; auxiliary gas: 55.00 psi; inlet voltage: -10.00 V; collision chamber outlet voltage: -10.00 V; data acquisition time: 4.00 min.
[0187] The pharmacokinetic results of epalrestat tablets are shown in Tables 18 to 22.
[0188] Table 18 Pharmacokinetic results of epalrestat tablets and reference preparations of Example 6
[0189]
[0190] Table 19 Pharmacokinetic results of epalrestat tablets and reference preparations of Example 7
[0191]
[0192] Table 20 Pharmacokinetic results of epalrestat tablets and reference preparations in Example 8
[0193]
[0194] Table 21 Pharmacokinetic results of epalrestat tablets and reference preparations in Example 9
[0195]
[0196] Table 22 Pharmacokinetic results of epalrestat tablets and reference preparations in Example 10
[0197]
[0198] The reference preparation is epalrestat tablets developed by Japan Alfalsa Pharmaceutical Co., Ltd. (Ono Pharmaceutical).
[0199] As shown in Tables 18 to 22, when the surfactants and disintegrants are different, the epalrestat tablets prepared in Examples 6 to 10 have a C max and AUC are different, among which, C of Examples 6 and 10 max The AUC of the drug can reach at least 1.5 times that of the reference drug, which is significantly better than that of the reference drug. It can be seen that when the surfactant is a combination of poloxamer 188 and polysorbate, and the disintegrant is a combination of carboxymethylcellulose calcium and cross-linked carboxymethylcellulose sodium, or a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone, C max and AUC were significantly improved, especially in Example 10, when the surfactant was a combination of poloxamer 188 and polysorbate, and the disintegrant was a combination of carboxymethylcellulose calcium and cross-linked carboxymethylcellulose sodium, its C max The AUC can be at least twice that of the reference preparation. The bioavailability is the highest.
Claims
1. An epalrestat pharmaceutical composition, characterized in that: The invention comprises the following components: epalrestat, a filler, a disintegrant, a surfactant and a binder, wherein the weight percentage of each component is as follows: epalrestat 25-65%, a filler 25-70%, a binder 2-8%, a disintegrant 2-8%, a surfactant 1-3%; the surfactant is poloxamer or a combination of poloxamer and other surfactants; the disintegrant is carboxymethylcellulose calcium, cross-linked carboxymethylcellulose sodium or a combination thereof, or a combination thereof with other disintegrants.
2. The epalrestat pharmaceutical composition according to claim 1, characterized in that The surfactant is poloxamer 188, a combination of poloxamer 188 and polysorbate, a combination of poloxamer 188 and sodium lauryl sulfate, and a combination of polysorbate and fatty acid glyceride.
3. The epalrestat pharmaceutical composition according to claim 1 or 2, characterized in that: The disintegrant is calcium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked sodium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked polyvinyl pyrrolidone, a combination of calcium carboxymethylcellulose and low-substituted hydroxypropyl cellulose, cross-linked sodium carboxymethylcellulose, a combination of cross-linked sodium carboxymethylcellulose and low-substituted hydroxypropyl cellulose, and a combination of cross-linked sodium carboxymethylcellulose and sodium starch glycolate.
4. The epalrestat pharmaceutical composition according to claim 2, characterized in that: When the surfactant is a combination of poloxamer 188 and polysorbate, the mass ratio of poloxamer 188 to polysorbate is 2:3-3:1, preferably 1:1-3:1; when the surfactant is a combination of poloxamer 188 and sodium dodecyl sulfate, the mass ratio of poloxamer 188 to sodium dodecyl sulfate is 1:1-3:2; when the surfactant is a combination of polysorbate and fatty acid glyceride, the mass ratio of polysorbate to fatty acid glyceride is 3:
2.
5. The epalrestat pharmaceutical composition according to claim 3, characterized in that: When the disintegrant is a combination of calcium carboxymethyl cellulose and cross-linked sodium carboxymethyl cellulose, the mass ratio of calcium carboxymethyl cellulose to cross-linked sodium carboxymethyl cellulose is 1:3 to 3:1, preferably 2:3 to 3:2; When the disintegrant is a combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone, the mass ratio of carboxymethylcellulose calcium to cross-linked polyvinyl pyrrolidone is 2:3 to 3:2; When the disintegrant is a combination of calcium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, the mass ratio of calcium carboxymethyl cellulose to low-substituted hydroxypropyl cellulose is 1:3 to 2:3; When the disintegrant is a combination of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, the mass ratio of cross-linked sodium carboxymethyl cellulose to low-substituted hydroxypropyl cellulose is 1:3 to 3:2; When the disintegrant is a combination of cross-linked sodium carboxymethyl cellulose and sodium starch glycolate, the ratio of cross-linked sodium carboxymethyl cellulose to sodium starch glycolate is 1:1 to 3:
2.
6. The epalrestat pharmaceutical composition according to any one of claims 1 to 5, characterized in that: Epalrestat 30-55%, silicified microcrystalline cellulose 35-60%, calcium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked sodium carboxymethylcellulose, a combination of calcium carboxymethylcellulose and cross-linked polyvinyl pyrrolidone 3-7%, poloxamer 188, a combination of poloxamer 188 and polysorbate, a combination of polysorbate and fatty acid glycerides 1.5-2.5%, and hydroxypropyl cellulose 3.5-6.5%.
7. The epalrestat pharmaceutical composition according to any one of claims 1 to 5, characterized in that: The invention comprises the following components: 40-50% epalrestat, 38-48% silicified microcrystalline cellulose, 4-5% combination of carboxymethylcellulose calcium and cross-linked sodium carboxymethyl cellulose, 1.8-2.2% combination of poloxamer 188 and polysorbate, and 4-6% combination of polysorbate and fatty acid glyceride; preferably: 40-50% epalrestat, 38-48% silicified microcrystalline cellulose, 4-5% combination of carboxymethylcellulose calcium and cross-linked sodium carboxymethyl cellulose, and 4-5% combination of carboxymethylcellulose calcium and cross-linked polyvinyl pyrrolidone, 1.8-2.2% combination of poloxamer 188 and polysorbate, and 4-6% combination of polysorbate and fatty acid glyceride.
8. The epalrestat pharmaceutical composition according to claim 6 or 7, characterized in that: In the combination of calcium carboxymethyl cellulose and cross-linked sodium carboxymethyl cellulose, the mass ratio of calcium carboxymethyl cellulose to cross-linked sodium carboxymethyl cellulose is 2:3-3:2, preferably 1:1; in the combination of calcium carboxymethyl cellulose and cross-linked polyvinyl pyrrolidone, the mass ratio of calcium carboxymethyl cellulose to cross-linked polyvinyl pyrrolidone is 2:3-3:2, preferably 1:1; in the combination of poloxamer 188 and polysorbate, the mass ratio of poloxamer 188 to polysorbate is 3:2, and in the combination of polysorbate and fatty acid glyceride, the mass ratio of polysorbate to fatty acid glyceride is 3:
2.
9. The method for preparing the epalrestat pharmaceutical composition according to claim 1, characterized in that: (1) sieving epalrestat, filler, disintegrant, surfactant and binder respectively; (2) According to the prescribed amount, the sieved epalrestat, filler, disintegrant, surfactant and binder are spheronized with a soft material made of a wetting agent to obtain micropellets, which are then dried and granulated to obtain epalrestat pharmaceutical composition granules; The particle size (D90) of epalrestat is <60 μm, preferably the particle size (D90) is <35 μm.
10. The epalrestat pharmaceutical composition according to any one of claims 1 to 8, characterized in that: The pharmaceutical composition is added with a lubricant, mixed evenly, and tableted. A proper amount of coating material is added as required, and after coating, tablets of the epalrestat pharmaceutical composition are obtained.
Citation Information
Cited By
Preparation process and application of high-purity epalrestat
CN121735878A
